Pengaruh Pembiayaan Mudharabah Dan Pembiayaan Musyarakah Terhadap Return Of Asset (Roa) Pada Bank Syariah Mandiri - Dewi, Ratih Komala (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
The study aims to determine the effect of Mudharabah Financing and Musyarakah Financing on Return of Assets (RoA) in Bank Mandiri Syariah in 2014-2018. The method of data collection in the subject of research was obtained by tabulating secondary data in the form of financial statements at Bank Mandiri Syariah in 2014 - 2018. The quantitative method of data analysis was done by processing SPSS software data in the form of classic assumption testing, testing F test statistics and testing t test to draw interesting conclusion. The results of this study indicate Mudharabah Financing and Musyarakah Financing have a positive influence on Return of Assets (RoA) in Bank Mandiri Syariah in 2014-2018 both partially and simultaneously.